SIMULASI AUTOMATIC TRANSFER SWITCH DAN AUTOMATIC MAINS FAILURE DENGAN PLC OMRON SYSMAC CP1E - Suhanto Suhanto (Journal of Mechanical Engineering and Mechatronics, 2019)
Electric power supply is the main requirement of equipment at the airport, therefore the reliability of the supply of power supplies is a top priority to support flight services. In addition to PLN as the main power supply the generator is used to supply a backup power supply. Automatic Transfer Switch (ATS) and Automatic Mains Failure (AMF) control systems are needed to regulate the switching of power supplies from PLN to Genset or vice versa. The ATS and AMF control systems use the Omron Sysmac CP1E PLC with a display using Easy Builder 8000 from Weintek which functions as an ATS and AMF monitor and control. Test results on ATS and AMF in manual and automatic modes, the system runs well.Keywords. Automatic Transfer Switch (ATS), Automatic Mains Failure (AMF), PLC